Pendampingan Pemanfaatan Peta Sosial Untuk Pembangunan Di Kampung Kuala Gasib Kabupaten Siak - Harapan Tua; Tito Handoko; Aisyah Nurterra (JOURNAL OF COMMUNITY SERVICES PUBLIC AFFAIRS, 2020)
The customary village is a government unit that is managed by the customary community and has the right to manage the territory (ulayat rights) and the life of the community in the environment of the customary village. Kampung Kuala Gasib was chosen to be one of the traditional villages in the Siak distric. The socio-cultural life of Kampung Kuala Gasib is heterogeneous, where there are many different tribes who live side by side, in the economic life of the people of Kuala Gasib Village, the majority of which are in the oil palm plantation sector and make oil palm the main commodity in this area. The purpose of this research is to see the socio-economic correlation with the level of social welfare based on the level of employment, level of education, social groups, and assets that the community owns to support their socio-economic life. This research method uses a descriptive qualitative approach, and the validity of the data uses the census method. The results showed that the welfare level of the community was still mostly in the middle to lower class, with the dominant occupation rate being farmers at 11% and those who did not work at 37%.